Study of hematological parameters among blood donors in Duhok city - Mizouri, Sawer Sabri (Zanco Journal of Medical Sciences (ZJMS), 2024)
Background and objective: Changes in peripheral blood parameters are commonly seen in physiological, stressful and pathological conditions. The aim of this research was to study the abnormalities in hematological parameters of the blood donors in Duhok blood banking center. Methods: This study was carried out at Duhok blood banking center, from 20th February, 2022, to July 1, 2022. The study included 1168 adult blood donors of both genders. A Complete blood count was performed by a three-part hematology analyzer and hematological parameters (Hb, HCT, PLT, WBC) were obtained from 1168 random blood donor samples. Open Epi program was used for data analysis; statistical significance was set at P <0.05 and 95% CL was accepted. Results: Out of 1168 donors, 243 donated for the first time and 925 donors were repeated donors and 1148 (98.29%) were male with females constituting only 20 (1.71%) of all donors. The donors’ age was between 18 and 68 years. Age is generally divided into five groups G1= (< 20 years) and G2= (20-29 years), G3= (30 -39 years), G4= (40- 49 years) and G5= (> 50 years). Most of the donors (31.21%) were in the age group (30 – 39 years) meanwhile the deferral rate was higher in this age group. Conclusion: It is evident from this study that abnormalities in hematological parameters are frequently seen amongst the blood donor population and frequently contributed to donor deferral and there is a need to maintain and keep hematology analyzer in the donor acceptance criteria.